Investigation on the Kinetic Feature of CI Acid Blue 106 Dyeing on Woolen Material - Farnaz Sadat Fattahi (Nanochemistry Research)
Woolen yarns are the main material for the fabrication of nanocomposite blended yarns, multilayer fabrics and nanostructure nonwovens for the textiles and garments. This study was started in an effort to search the kinetic and thermodynamic characteristics of CI Acid Blue 106 (A leveling acid dye) on woolen yarns. Various models (zero order, first order, second order, Parabolic, cegarra–Puente, and modified cegarra–puente models) were used to recognize an appropriate dyeing apparatus. It was established that the modiﬁed cegarra-puente model top fitted to the studied information with the maximum correlation (R2≥0.999). The dyeing-rate constant, the half dyeing times, rise time and fixation time were then considered. Also, thermodynamic parameters, such as the activation energy (Ea), were considered.